Paranoplocephala buryatiensis Haukisalmi, Hardman, Hardman, Laakkonen, Niemimaa & Henttonen 2006 - Haukisalmi, Voitto; Henttonen, Heikki; Hardman, Lotta; Hardman, Michael; Laakkonen, Juha; Murueva, Galina; Niemimaa, Jukka; Shulunov, Stanislav; Vapalahti, Olli (Zenodo, 2009)
Paranoplocephala buryatiensis Haukisalmi, Hardman, Hardman, Laakkonen, Niemimaa & Henttonen, 2006 P. buryatiensis , described from Buryatian material, is primarily a parasite of Myodes rufocanus (Haukisalmi et al. 2007a), although it was found occasionally in Microtus fortis in the present material. Its known range spans from Buryatia to north-eastern Siberia. However, it does not occur in the westernmost populations of Myodes rufocanus in northern Fennoscandia (Haukisalmi et al. 2007a). P. buryatiensis is morphologically and genetically closely related to P. longivaginata Chechulin & Gulyaev, 1998 from Myodes rutilus (below); they form a strongly supported clade in the mtDNA phylogenies (Fig. 2 and Haukisalmi et al. 2007a). Haukisalmi et al. (2007a) provided evidence for phylogenetic codivergence of P. buryatiensis and P. longivaginata with their primary hosts. P. buryatiensis occurred in Myodes rufocanus at four of the eight study sites, the prevalence in Pasolskaya (43%) being higher than in the other sites (0-10%). It also occurred in Microtus fortis at two study sites, where it also parasitized the primary host Myodes rufocanus . Type specimen: USNPC 97137 from Myodes rufocanus (Pasolskaya); paratype specimen: USNPC 97138 from M. rufocanus (Pasolskaya); voucher specimen: US- NPC 97139 from Microtus fortis (Kamensk). Published as part of Haukisalmi, Voitto, Henttonen, Heikki, Hardman, Lotta, Hardman, Michael, Laakkonen, Juha, Murueva, Galina, Niemimaa, Jukka, Shulunov, Stanislav & Vapalahti, Olli, 2009, Review of tapeworms of rodents in the Republic of Buryatia, with emphasis on anoplocephalid cestodes, pp. 1-18 in ZooKeys 8 (8) on page 9, DOI:10.3897/zookeys.8.58, http://zenodo.org/record/576440